Nuove piazze commerciali alla fine del Medioevo: la Calabria e la Via della Seta dopo la nascita dell’Impero Ottomano - Procopio, Sarah (Occhialì, 2020)
During the 15th century, Calabria succeeded as an important exporter of raw silk in the Mediterranean arena. Even if its territory had mulberry plantations since the Byzantine period, only in the 15th century Calabrian raw silk began to be purchased by the enterprises which supplied the silk industry in Northern Italy. This paper aims to underline the dynamics which enabled Calabria, only at the end of the Middle Ages and not before, to rise thanks to its silk production. Indeed, while the Ottomans emerged in the Levant, setting new trade conditions to Western merchants, the Neapolitan Kingdom promoted the arrival of foreign merchants in the Mezzogiorno. Thus, the main goal of the paper is to show how the rise of the Ottoman Empire indirectly favoured the trade of Calabrian raw silk.